Checkpoint Inhibitor–Associated Arthritis: A Systematic Review of Case Reports and Case Series. Issue 8 (28th December 2021) - Ghosh, Nilasha; Tiongson, Michael D.; Stewart, Carolyn; Chan, Karmela K.; Jivanelli, Bridget; Cappelli, Laura; Bass, Anne R.
Abstract : Supplemental digital content is available in the text. Abstract : Objective: We performed a systematic literature review to identify all reports of immune checkpoint inhibitor–associated inflammatory arthritis to describe it phenotypically and serologically. Methods: PubMed, Embase, and Cochrane databases were searched for reports of musculoskeletal immune-related adverse events secondary to ICI treatment. Publications were included if they provided individual patient level data regarding the pattern of joint involvement. Descriptive statistics were used to summarize results. Results: A total of 4339 articles were screened, of which 67 were included, encompassing 372 patients. The majority of patients had metastatic melanoma (57%), and they were treated with anti-PD1 or anti-PDL1 therapy (78%). Median time to onset of arthritis was 4 months (range, 1 day to 53 months). Forty-nine percent had polyarthritis, 17% oligoarthritis, 3% monoarthritis, 10% arthralgia, and 21% polymyalgia rheumatica. More than half of patients were described as having a "rheumatoid arthritis–like" presentation. Nine percent tested positive for rheumatoid factor or anti–cyclic citrullinated peptide antibodies. Seventy-four percent required corticosteroids, and 45% required additional medications. Sixty-three percent achieved arthritis control, and 32% were ultimately able to discontinue antirheumatic treatments. Immune checkpoint inhibitors were continued in 49%, transiently withheld in 11%, and permanently discontinued due to musculoskeletal immune-related adverse events in 13%. Conclusions: Half of reported immune checkpoint inhibitor–associated arthritis cases present with polyarthritis (often RA-like), but only 9% are seropositive. Polymyalgia rheumatica is also common. Most patients respond to steroids alone, but about half require additional medications. Further studies are needed to determine long-term musculoskeletal outcomes in these patients, and the impact of arthritis treatment on cancer survival.